Forward secure delay-tolerant networking - Schwarz-Rüsch, Signe; Schürmann, Dominik; Wolf, Lars; Kapitza, Rüdiger (CHANTS 2017 - Proceedings of the 12th Workshop on Challenged Networks, co-located with MobiCom 2017, 2017)
Delay-Tolerant Networks exhibit highly asynchronous connections often routed over many mobile hops before reaching its intended destination. The Bundle Security Protocol has been standardized providing properties such as authenticity, integrity, and confidentiality of bundles using traditional Public-Key Cryptography. Other protocols based on Identity-Based Cryptography have been proposed to reduce the key distribution overhead. However, in both schemes, secret keys are usually valid for several months. Thus, a secret key extracted from a compromised node allows for decryption of past communications since its creation. We solve this problem and propose the first forward secure protocol for Delay-Tolerant Networking. For this, we apply the Puncturable Encryption construction designed by Green and Miers, integrate it into the Bundle Security Protocol and adapt its parameters for different highly asynchronous scenarios. Finally, we provide performance measurements and discuss their impact.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Delay-Tolerant Networking; Dtn; Forward secrecy; Puncturable Encryption